Pengaruh Corporate Social Responsibility, Firm Size terhadap Nilai Perusahaan dengan Profitabilitas Sebagai Variabel Intervening - Novita, Safira; Ainiyah, Nur (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2025)
The purpose of this study is to determine the effect of the independent variable on the dependent variable and to test whether the intervening variable can affect the relationship between the independent variable and the dependent variable. The independent variables in this study are Corporate Social Responsibility (CSR) and firm size, while the dependent variable used is firm value, and the intervening variable used is profitability. The technique in determining the sample uses purposive sampling technique. Many of the samples used for this study are 15 Go Public mining companies listed on the Indonesia Stock Exchange for the 2018-2020 period. This research hypothesis was tested using Partial Least Square (PLS). The conclusion obtained from the results obtained in this study is that it explains that Corporate Social Responsibility (CSR) and firm size have a significant effect on firm value, while profitability has no effect on firm value, and profitability is proven unable to support the relationship between Corporate Social Responsibility (CSR) and firm size on firm value.